Identification of the Replication Origins from Cyanothece ATCC 51142 and Their Interactions with the DnaA Protein: From In Silico to In Vitro Studies - Huang, He; Song, Cheng-Cheng; Yang, Zhi-Liang; Dong, Yan; Hu, Yao-Zhong; Gao, Feng (Frontiers in Microbiology, 2015)
Based on the complete genome of Cyanothece ATCC 51142, the oriCs of both the circular and linear chromosomes in Cyanothece ATCC 51142 have been predicted by utilizing a web-based system Ori-Finder. Here, we provide experimental support for the results of Ori-Finder to identify the replication origins of Cyanothece ATCC 51142 and their interactions with the initiator protein, DnaA. The two replication origins are composed of three characteristically arranged DnaA boxes and an AT-rich stretch, and the oriC in the circular chromosome is followed by the dnaN gene. The dnaA gene is located downstream of the origin of the circular chromosome and it expresses a typical DnaA protein that is divided into four domains (I, II, III, IV), as with other members of the DnaA protein family. We purify DnaA (IV) and characterize the interaction of the purified protein with the replication origins, so as to offer experimental support for the prediction. The results of the electrophoretic mobility shift assay and DNase I footprint assay demonstrate that the C-terminal domain of the DnaA protein from Cyanothece ATCC 51142 specifically binds the oriCs of both the circular and linear chromosomes, and the DNase I footprint assay demonstrates that DnaA (IV) exhibits hypersensitive affinity with DnaA boxes in both oriCs.